2021
DOI: 10.48550/arxiv.2109.06229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dark Energy at early times and ACT: a larger Hubble constant without late-time priors

Vivian Poulin,
Tristan L. Smith,
Alexa Bartlett

Abstract: Recent observations using the Atacama Cosmology Telescope (ACT) have provided ground-based cosmic microwave background (CMB) maps with higher angular resolution than the Planck satellite. These have the potential to put interesting constraints on models resolving the 'Hubble tension'. In this paper we fit two models of Early Dark Energy (EDE) (an increase in the expansion rate around matter/radiation equality) to the combination of ACT data with large-scale measurements of the CMB either from the WMAP or the P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 79 publications
1
34
0
Order By: Relevance
“…Meanwhile, the preference for a non-zero EDE component is strengthened (as found in [56,69,81]): we find the marginalized constraint f EDE = 0.108 +0.053 −0.023 when ACT is included, compared to f EDE = 0.099 +0.056 −0.041 without ACT data. However, the f EDE posterior distribution in Fig.…”
Section: Edssupporting
confidence: 51%
See 1 more Smart Citation
“…Meanwhile, the preference for a non-zero EDE component is strengthened (as found in [56,69,81]): we find the marginalized constraint f EDE = 0.108 +0.053 −0.023 when ACT is included, compared to f EDE = 0.099 +0.056 −0.041 without ACT data. However, the f EDE posterior distribution in Fig.…”
Section: Edssupporting
confidence: 51%
“…The ACT collaboration analyzed the EDE model in [56] and found that ACT data combined with low-Planck T T data ( < 650, similar to WMAP ) mildly prefer a non-zero f EDE at ≈ 3σ significance (see also [69] and [70]). When combining ACT with the full Planck data set, this preference is no longer seen, due to the dominant statistical weight of Planck (which does not prefer EDE on its own).…”
Section: Constraints From Datamentioning
confidence: 99%
“…During the NEDE phase transition ψ ≡ √ 2|Ψ 0 | → v Ψ , which implies a breaking of the global U(1) L and, as shown before, gives a mass to the active neutrinos. From (15) we derive the vacuum condition…”
Section: Hot Nede and Neutrino Mass Generationmentioning
confidence: 99%
“…It has been known for a while now, that one of the most promising avenues for resolving the Hubble tension in cosmology is an extra component of DE, which decays just before recombination. In the first proposal of this type, called early dark energy (EDE) [10][11][12][13][14][15], the decay of this extra component of DE happened just before recombination in a second-order rollover of an axion-like scalar field (also see [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] for related work and [33][34][35][36][37][38][39][40][41] for other early-time approaches). But without fine-tuning of the axion potential the EDE component does not dilute fast enough after the transition to be in agreement with data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation